The Utilization of Digital Media as a Learning Medium for Akidah Akhlak - Dias Maulana; Layla Mardliyah (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2026)
Akidah Akhlak learning in the modern era demands the innovative utilization of digital media to overcome student boredom frequently caused by the dominance of conventional teaching methods. This study aims to examine the effectiveness of utilizing web-based digital media specifically using Google Sites as an interactive learning medium to boost students' learning outcomes. This quantitative research employed a pre-experimental design with a one-group pretest-posttest model. The research subjects involved 26 students of Class VIII E at MTs Al-Ittihaad Ma’arif NU 1 Purwokerto, selected through the intact group technique. Data collection relied on learning outcome test instruments, which were subsequently analyzed using descriptive statistics and the Normalized Gain (N-Gain) test. Empirical data analysis proved a significant escalation in the students' average learning outcomes, surging sharply from 45.77 in the pre-test to 89.62 in the post-test. Furthermore, the effectiveness test yielded an N-Gain coefficient of 0.81, which is classified into the "High" category. Based on these findings, it is concluded that the utilization of digital media is proven to be highly effective, valid, and feasible as a learning instrument to optimize students' conceptual understanding and academic achievements in the Akidah Akhlak subject.